Legal Liability for Copyright Infringement of Video Content Uploaded by Malaysian Individuals for Commercial Purposes on TikTok - Risca Selfeny; Muthia Sakti; Iwan Erar Joesoef (Yayasan Cerdas Pedia Indonesia, 2026)
The rapid evolution of digital technology, specifically the TikTok platform, has precipitated a surge in unauthorized use and modification of video content for cross-border commercial exploitation, as exemplified by the legal dispute between dr. Leo and various Indonesian content creators. This research aims to analyze the specific legal sanctions for digital copyright infringement and to formulate a prescriptive application of Article 5 of Law Number 28 of 2014 on Copyright to ensure legal certainty for creators. Utilizing a normative juridical research method with statutory and case-based approaches, this study examines national positive laws alongside international legal instruments, including the Berne Convention and the WIPO Copyright Treaty. The findings demonstrate that unauthorized modification constitutes a breach of both moral and economic rights, punishable by criminal, civil, and administrative sanctions. Nevertheless, enforcement remains hindered by jurisdictional complexities and suboptimal Mutual Legal Assistance (MLA) frameworks between Indonesia and Malaysia. Ultimately, this research concludes that a rigorous application of Article 5, bolstered by enhanced international cooperation and digital platform accountability, is imperative to safeguard intellectual integrity and ensure justice for creators in the digital age.